Safe New Approach to the Lingual Flap Management in Mandibular Augmentation Procedures: The Digitoclastic Technique. Issue 5 (October 2017) - Pistilli, Roberto; Checchi, Vittorio; Sammartino, Gilberto; Simion, Massimo; Felice, Pietro
Abstract : Purpose: This article describes the digitoclastic technique, an innovative procedure for coronal displacement of the lingual flap. The new technique has the potential to obtain primary flap closure without surgical risks to the anatomical structures on the lingual side of the mandible. Materials and Methods: Reconstruction of an atrophic mandible with guided tissue regeneration (guided bone regeneration) and implant placement is described, using the digitoclastic technique to displace the lingual flap coronally. Results: Coronal flap displacement was sufficient to obtain complete passive coverage of the grafted area. No bleeding or neurosensory complications were recorded, and no membrane exposure occurred. Conclusions: The digitoclastic technique reduces the risk of damage to the lingual nerve and minimizes the amount of bleeding during surgery, allowing progressive and controlled retraction of the flap until the desired detachment is achieved.